2014
DOI: 10.1021/es500073r
|View full text |Cite
|
Sign up to set email alerts
|

Speciation of Sulfur in Biochar Produced from Pyrolysis and Gasification of Oak and Corn Stover

Abstract: The effects of feedstock type and biomass conversion conditions on the speciation of sulfur in biochars are not well-known. In this study, the sulfur content and speciation in biochars generated from pyrolysis and gasification of oak and corn stover were determined. We found the primary determinant of the total sulfur content of biomass to be the feedstock from which the biochar is generated, with oak and corn stover biochars containing 160 and 600–800 ppm sulfur, respectively. In contrast, for sulfur speciati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
77
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(85 citation statements)
references
References 51 publications
6
77
1
1
Order By: Relevance
“…The up-or down-regulation of both N and S limits the function of other nutrients (McGrath and Zhao, 1996). The application of BC may also serve as an additional balanced source of S and N provisions (Elad et al, 2011;Cheah et al, 2014;Waqas et al, 2014). The role of both nutrients is central and interrelated to amino acid biosynthesis and, hence, proteins (McGrath and Zhao, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…The up-or down-regulation of both N and S limits the function of other nutrients (McGrath and Zhao, 1996). The application of BC may also serve as an additional balanced source of S and N provisions (Elad et al, 2011;Cheah et al, 2014;Waqas et al, 2014). The role of both nutrients is central and interrelated to amino acid biosynthesis and, hence, proteins (McGrath and Zhao, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…High production temperature increases the pH value of biochars probably as a consequence of the relative concentration of non-pyrolyzed inorganic elements that are already present in the original feedstocks (Novak et al 2009). Biochar's alkalinity can be attributed to four broad categories: surface organic functional groups, carbonates, soluble organic compounds and other inorganic alkalis including oxides, hydroxides, sulfates, sulfides, and orthophosphates (Cheah et al 2014). Increased pH of biochar amended acid soils may help to reduce Al toxicity and increase P availability.…”
Section: Physical Characterization Of Biocharsmentioning
confidence: 99%
“…In this study sulfur content of pyrolyzed biochars varied from slightly over 0.5% (corn cob) to about 2% (water hyacinth and domestic organic waste). Cheah et al (2014) reported that pyrolyzed biochars (500 -600°C) mainly contain sulfate (77 -100%), organosulfur, and sulfide whereas gasification biochars contain 73 -100% organosulfur.…”
Section: Carbon Content and Nutrient Status Of Feedstock And Biocharmentioning
confidence: 99%
“…Extensive work has been published on the individual production of biochar or syngas [19,20]. However, attempts to simultaneously produce biochar in biomass gasifier systems has been rare and challenging [21]. For instance, Qian et al [22] tested a fluidized bed gasifier for the production and characterization of biochar.…”
Section: Introductionmentioning
confidence: 99%